Analysis of the Presentation of Financial Statements and the Morality of Apparatus on the Potential of Fraud in Village Financial Management - Maemunah, Mey; Hernawati, Nopi; Kuntorini, Ririn Sri (KnE Social Sciences, 2023)
Referring to Permendagri (Minister of Home Affairs Regulation) No. 20 of 2018, the presentation of transparent and accountable financial reports can serve as a deterrent against fraud in village funds. Furthermore, the moral support of village officials can aid in the proper management of funds in accordance with the provisions outlined in Permendagri. Thus, the presentation of financial reports is expected to provide accurate information and assist users in their decision-making processes. The research method employed in this study is a case study with a descriptive analysis approach. Nonprobability sampling with saturated samples is utilized as the sampling technique. Data collection techniques involve observation, in-depth interviews, and documentation. The results indicate that the presentation of financial statements in Karyalaksana Village and Lampegan Village is considered satisfactory. Similarly, the level of moral conduct among the village officials ranges from conventional to post-conventional, thereby reducing the potential for fraud in village financial management. Keywords: financial statement presentation, morality, fraud potential